Evaluasi Kepuasan Pelayanan Publik Studi Kasus Pada PT. Jamsostek (Persero) - Rahman, Abdul (Business Administration Study Program - Universitas Katolik Parahyangan, 2009)
Increasing and maintaining a service quality are not an easy job, moreover if thereare involving some division in delivering the services. JPK programme, as one of thepublic service programme in health, which are organized by PT jamsostek (Persero),using the trhee party pattern which are involving three institution, such as BadanPenyelenggara (PT Jamsostek), Provider (Health Care Organizer) dan Recipient (cor-poration dan employee) as their customer. The three party pattern is a complex modelsince each involved institutions have their own potential. Interaction among the threeinstitution will come out a potential side effect problem, which in the end affectedthe quality of the delivered services. In evaluating the satisfaction of the deliveredservices objectively, in tem of increasing and maintaining the servicesâ quality, thenthe aim of this research.Keywords: Program JPK, Tripartit, Evaluasi, Pengukuran, Kepuasan Konsumen